Environmental economics : a critical overview - Gilpin, Alan. (Chichester ; New York : John Wiley, 2000)
This book stress the links between economic concepts and real world issues and deals with population, natural resources, valuation, environmental regulation, economic instruments, cost benefit analysis, waste, water resources, air pollution, global warming, biodiversity and world trade.
Includes bibliographical references (p. 305]-321) and indexes.
aia 3/05/13
Loan
Keywords: Sustainable development; Environmental economics